Orexin A Differentially Influences the Extinction Retention of Recent and Remote Fear Memory - Shi, Le; Chen, Wenhao; Deng, Jiahui; Chen, Sijing; Han, Ying; Khan, Muhammad Z.; Liu, Jiajia; Que, Jianyu; Bao, Yanping; Lu, Lin; Shi, Jie (Frontiers in Neuroscience, 2018)
Recently the role of the orexin system in the learning and memory, especially orexin A, which could enhance fear memory through regulating the activity of amygdala, has drawn considerable attention. However, the relationship between orexin A and extinction memory remains unclear. To investigate the effect of orexin A on extinction memory in humans, we recruited forty-three male subjects and divided them into a recent group and remote group. After acquiring Pavlovian fear conditioning, individuals in recent group experienced fear extinction 24 hours after acquisition, and remote group underwent extinction two weeks later. Meanwhile, plasma orexin A levels before extinction were measured by enzyme-linked immunosorbent assay. Both groups received memory test 24 hours after fear extinction. The results showed that both recent and remote groups successfully acquired fear conditioning and had spontaneous recovery at test. In particular, the correlational analysis indicated that orexin A levels before extinction were negatively associated with fear responses during test only in recent group, but not in remote group. Moreover, individuals with high orexin A levels still kept low fear responses after extinction in recent group by subgroup analyses. The results suggest that orexin A could influence the retention of recent fear memory extinction, without affecting remote fear extinction. These findings remind us the orexin system can be a potential treatment target for fear-related disorders, and the mechanisms of recent and remote fear extinction may be different.